Exploring the application of self-directed and cooperative learning in information systems education: a critical analysis - Joshua Ebere Chukwuere (Journal of Science and Education (JSE), 2023)
Learning is a continuous process of acquiring knowledge. Information systems (IS) is a sub-discipline of computing discipline with a focus on providing theory and practical teaching and learning opportunities and experience for students in the area of managing computing resources in an organization and society at large. The application of self-directed and cooperative learning in information systems (IS) education has been an area of interest for researchers and educators. Self-directed learning emphasizes the learner's autonomy, while cooperative learning emphasizes collaboration and communication among learners. This paper presents a critical analysis involving self-directed and cooperative learning in IS education through a rapid review of the application of these learning approaches in IS teaching and learning. This study used a rapid review in searching, identifying, and analyzing relevant peer-review papers in critically analyzing the application of self-directed and cooperative learning in IS teaching and learning process. The analysis was done through a systematic approach reviewing relevant literature and identifying the benefits, challenges, and implications of self-directed and cooperative learning in IS education. The data analysis followed a rapid review approach to reaching the findings. The study revealed the meaning of SDL and CL and their application in IS teaching and learning process. The study also found different models that encourage the application of SDL and CL in IS teaching and learning process. The paper concludes with recommendations for IS educators and suggestions for future studies.